2007
DOI: 10.3998/ark.5550190.0008.f01
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium hydrogensulfate as an efficient and heterogeneous catalyst for preparation of aryl 14H-dibenzo[a,j]xanthene derivatives under thermal and solvent-free conditions

Abstract: A new, one-pot, simple thermally efficient and solvent-free method for the preparation of aryl 14H-dibenzo [a,j]xanthene derivatives by condensation of β-naphthol and substituted benzaldehydes using aluminium hydrogensulfate Al(HSO 4 ) 3 as an inexpensive heterogeneous and reusable catalyst is described. This method has the advantages of high yields, a cleaner reaction, simple methodology, short reaction times, ambient pressure, easy workup and greener conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…These derivatives have received wide attention for their synthesis due to their biological, industrial and therapeutic applications [21]. Xanthene derivatives have been synthesized in a variety of ways [22] in the presence of different catalysts such as, Yb(OTf)3 [23], InCl3 [24], Al(HSO4)3 [25], nano-TIO2 [26], NaHSO4 [27], cyanuric chloride [28], Amberlyst-15 [29], heteropoly acids [30], silica sulfuric acid [31], molecular iodine [32], sulfamic acid [33], P-TSA [34], and AcoH-H2SO4 [35]. Hossein and Oskooie et al reported the synthesis of 1,8-dioxooctahydroxanthenes using cellulose sulfonic acid in an excellent yields under solvent-free conditions [21].…”
Section: Introductionmentioning
confidence: 99%
“…These derivatives have received wide attention for their synthesis due to their biological, industrial and therapeutic applications [21]. Xanthene derivatives have been synthesized in a variety of ways [22] in the presence of different catalysts such as, Yb(OTf)3 [23], InCl3 [24], Al(HSO4)3 [25], nano-TIO2 [26], NaHSO4 [27], cyanuric chloride [28], Amberlyst-15 [29], heteropoly acids [30], silica sulfuric acid [31], molecular iodine [32], sulfamic acid [33], P-TSA [34], and AcoH-H2SO4 [35]. Hossein and Oskooie et al reported the synthesis of 1,8-dioxooctahydroxanthenes using cellulose sulfonic acid in an excellent yields under solvent-free conditions [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, these reported methods have many disadvantages, such as harsh reaction conditions, low yields, prolonged reaction times and require the use of excessive quantities of reagents and toxic solvents. To overcome these limitations, the reaction has recently been improved by mixing βnaphthol with aldehydes in the presence of catalysts, such as natural acidic ionic liquid immobilized on magnetic silica [11], task specific dicationic acidic IL [12], MCM-41@Schiff Base-Mn(OAc) 2 in water [13], Amberlyst-15 [14], LiBr [15], sulfamic acid [16], p-TSA [17], I 2 [18], Fe(HSO 4 ) 3 [19], BF 3 •SiO 2 [20], oxalic acid [21], dipyridine cobalt chloride [22], wet cyanuric acid [23], silica-supported perchloric acid [24], Al(HSO 4 ) 2 [25], SelectfluorTM [26], hydrochloric acid or phosphoric acid [27], H 2 SO 4 in acetic acid as solvent [28] and silica sulfuric acid [29]. These methods suffer from one or more disadvantages, such as drastic reaction conditions, long reaction times, a need for special apparatus and the use of hazardous solvents.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to a helpful review of literature in this publication, Singh and coworkers 1 developed an eco-friendly solventfree condensation method to obtain 14-aryl-or alkyl-14H-dibenzo [a, j] xanthenes using P2O5 or InCl3 as catalysts. For the synthesis of 14-aryl-14H-dibenzo [a, j] xanthene derivatives, Geng-Chen Li, has used aryl aldehydes, and freshly prepared expanded graphite as a catalyst 10 , while Hamid Reza Shaterian et al, reported the use of ferric hydrogen sulfate and aluminum hydrogen sulfate as catalysts 11,12 . Carbon tetra bromide (CBr4) 13 , and polyvinyl poly pyrrolidine-supported boron trifluoride (PVPP-BF3) 14 were the other important catalysts used for the synthesis of dibenzo xanthenes.…”
Section: Introductionmentioning
confidence: 99%